Determination of (-)-epigallocatechin-3-gallate octaacetate and its metabolites in plasma of rats for pharmacokinetic study by ultra-performance-liquid-chromatography coupled to quadrupole-time-of-flight-mass-spectrometry - Chu, Kai On; Man, Gene Chi Wai; Hung, Sze Wan; Chan, Tak Hang; Lee, Wai Yip Thomas; Chan, Kwok Ping; Pang, Chi Pui; Wang, Chi Chiu (Frontiers in Pharmacology, 2022)
(-)-Epigallocatechin-gallate octaacetate (pro-EGCG), a prodrug of epigallocatechin-gallate (EGCG), has been used for pre-clinical study for the treatment of endometriosis. A validated analytical method has been developed for the determination of plasma pro-EGCG and its metabolites after oral administration using ultra-performance-liquid-chromatography coupled to quadrupole-time-of-flight-mass-spectrometry (UPLC-Qtof-MS). This method is more robust, rapid, sensitive, simpler, and able to detect pro-EGCG metabolites compared to our previous method. Pro-EGCG in the plasma was stabilized from rapid degradation by formic acid, extracted by isopropanol/methyl-tert-butyl ether mixture, separated by UPLC core column, and quantified by an exact mass method with Qtof-MS. The lower limit of quantification (LLOQ), intra-day and inter-day precision, and accuracy for the range of 0.01 – 2.5 µg/mL were within acceptable limits. The sensitivity was improved by 25 folds using pro-EGCG ammonium adduct [M+NH4]+. This is the first report on the pharmacokinetics of oral administration with maximum-concentration (Cmax) was 0.067 ± 0.04 µg/mL, time-of-maximum-concentration (Tmax) was 1.33 hours, area-under-curve (AUC) was 0.20 ± 0.05 hr × µg/mL, and elimination-rate was 0.20 ± 0.11 hr-1. The pharmacokinetic profiles of pro-EGCG metabolites, (-)-epigallocatechin-gallate (EGCG) diacetates and EGCG triacetates, were also presented. This method is robust, rapid, and sensitive for the pharmacokinetic study of pro-EGCG and metabolites.